Normas sobre trazabilidad de los comerciantes en el entorno digital europeo - Flaquer Riutort, Juan (2024)
Contracting through digital intermediation platforms has experienced spectacular and continuous progress in recent years. One of the main problems that consumers face in this field is the precise identification of the person with whom they establish the exchange relationship, since, relatively frequently, the intervention of the platform itself confuses the user about of the real identity of the person with whom a certain good and/or service is truly contracted or acquired. In this work, the author analyzes the new informative duties imposed in this sense on platforms in the European community framework, essentially aimed at offering a greater degree of consumer protection, and among which the precise identification of the person with whom you contract, such as their status as a merchant or not, which is especially relevant for the purposes of the eventual application of consumer protection regulations. At the same time, the degree of compliance that, with respect to these informative duties, is observed in some of the platforms with the greatest implementation in the digital market.